Revitalisasi Ekonomi Pasca Pandemi COVID-19: Analisis Strategi Pemberdayaan UMKM Berbasis Digital Menuju 2025 - Shelvyna Rikantasari (Journal of Islamic Banking, 2026)
The COVID-19 pandemic has significantly impacted the economic sector, particularly Micro, Small, and Medium Enterprises (MSMEs), which faced severe pressure in terms of operations and competitiveness. This article aims to analyze digital-based empowerment strategies for MSMEs as part of post-pandemic economic revitalization efforts toward 2025. This study employs a qualitative approach through literature analysis and secondary data from academic publications, government reports, and recent case studies. Findings indicate that the success of MSME empowerment is largely determined by synergy between the government, private sector, and community in building an inclusive digital ecosystem. Digital literacy, access to technology, and business mentoring are key factors in promoting sustainability and competitiveness for MSMEs in the post-pandemic era. This study recommends a collaborative model that integrates public policy, technological innovation, and community institutional strengthening as a strategic direction for future MSME empowerment.